FRI0360 Analysis of endocannabinoid system elements and related inflammatory molecules in peripheral blood leukocytes of patients with systemic sclerosis. (15th June 2017) - Perez-Sanchez, C; Ortega-Castro, R; del, C Río; Aguirre, MA; Ruiz-Limon, P; Barbarroja, N; Jimenez-Gomez, Y; Rosa, I Arias-de la; Abalos-Aguilera, MC; Collantes-Estevez, E; Muñoz, E; Lopez-Pedrera, C
Abstract : Background: The Endocannabinoid system (ECS) is a potential target for treatment of systemic sclerosis (SSc). Several cytokines/chemokines have been implicated in the induction of fibrosis in SSc, but their profile in peripheral blood mononuclear cells (PBMCs), and a relationship among specific inflammatory mediators, ECS, and organ involvement has not been established Objectives: To analyze ECS elements and related inflammatory molecules in PBMCs of SSc patients, and evaluate their relationship with the clinical profile of the disease Methods: 24 SSc patients [including 5 Pre-SSc, 13 limited cutaneous SSc (lc-SSC) and 6 difusse cutaneous SSc (dc-SSc)] and 24 healthy donors (HD) were included. Purified PBMCs were used for analysis of gene expression of molecules belonging to the ECS: CB1, CB2, GPR55, PPARγ, FAAH, MAGL and TRPV. Inflammatory mediators were evaluated in PBMCs by RT-PCR. Clinical evaluation of patients was performed and correlation/association studies were developed Results: Cannabinoid type-2 receptor, GPR55 and TRPV1 gene expression were reduced in PBMCs of SSc patients, while FAAH levels were elevated. CB2 levels were lower in lc-SSc in relation to sc-SSc, and related to the presence of auto-antibodies anti-Scl70. Concomitantly, levels of FAAH were higher in dc-SSc in relation to lc-SSc, and associated to the presence of anti-centromere antibodies. A relationship between the low levels of GPR55 and the presence of pulmonary arterial hypertension was further demonstrated. Reduced levels of TRPV were associated to pulmonary involvement. Analysis of the inflammatory profile showed significantly increased PBMC expression levels of IL-1, IL-8, IL-12, MCP-1, TGFβ, TNFα, and VEGF-A in SSc. In addition, in the patient's group of Pre-SSc, specific elevation in various cytokines was demonstrated (i.e.IL-1, IL-17, VEGF-A), suggesting that these cytokines might act as early biomarkers of disease development. Patient's positive for anti-centromere antibodies showed increased expression of IL-4, IL-17 and MCP-1 in relation to those positive for anti-scl70. PBMCs expression levels of TGFβ, IL-12 and MCP-1 were higher in lc-SSc compared to ds-SSc. Interestingly, we observed a direct relationship between levels of these three cytokines and the occurrence of pulmonary hypertension, a pathology more frequent in lc-SSc, thus suggesting a role for these inflammatory molecules in pulmonary involvement in this form of the disease. Correlation studies demonstrated an interrelation among deregulated expression of various molecules belonging to the ECS (i.e. FAAH, GPR55 and TRPV1) and inflammatory mediators over-expressed in serum and immune cells (i.e. CRP, ESR, MCP-1, TNFα and VEGF-A) Conclusions: SSc patients show altered gene profile of ECS and inflammatory mediators in PBMCs, which might allow the discrimination between limited and diffuse forms of the disease, and are associated with the presence of specific auto-antibodies and the internal organ involvement. Our overall data suggest an appealing potential target of ECS for treatment of SSc, as it seems to be related to the inflammatory profile Acknowledgements: CTS-794 and ISCIII (PI15/01333 and RIER RD16/0012/0015 Disclosure of Interest: None declared